MAIN CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS OF HIV/AIDS PATIENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
HIV infection is one of the most critical public health issues in the world, and it is ranked as such because of its prevalence, socio-economic consequences, absence of specific prevention methods, and the cost of treatment. In Uzbekistan, the prevalence of HIV is rising, and this is the reason why epidemiological surveillance and prevention are critical.